An art therapy intervention for cancer patients in the ambulant aftercare – results from a non‐randomised controlled study. (18th January 2013) - Geue, K.; Richter, R.; Buttstädt, M.; Brähler, E.; Singer, S.
An art therapy intervention for cancer patients in the ambulant aftercare – results from a non‐randomised controlled study: Art therapy in psycho‐oncology is gaining increasing importance, but systematic evaluations of its effects are rare. The aim of this study is to investigate the effects of an art therapy intervention for cancer patients in ambulant aftercare on psychological distress and coping. The intervention consisted of 22 sessions. At three points of measurement (t1: before intervention, t2: following intervention, t3: 6 months after t2), participants responded to questionnaires (Freiburg Questionnaire on Coping with Illness, Perceived Adjustment to Chronic Illness Scale, Hospital Anxiety and Depression Scale). A group of haemato‐oncological patients served as the comparison group (CG). Pre–post comparisons and analyses of variance were applied for statistical analysis. Relevant confounders were controlled. Fifty‐four patients (intervention group, IG) with various cancer diagnoses completed the intervention. One hundred and twenty‐nine data sets were available for the CG. Analyses of variance included group membership (IG vs. CG) and the following factors: gender, other psychosocial help and major life events. None of these variables was a predictor for changes in depression, anxiety and coping. Therefore, we could not prove intervention effects over time. Our results contradict those of preliminary studies and raise important questions. Further work on evaluating art therapy is necessary to explore which intervention concepts in which setting at which treatment stage show significant effects. Therefore, controlling for relevant confounders is needed.